The PERFORMANSI PADI GREEN SUPER RICE YANG ADAPTIF PADA LAHAN SAWAH TADAH HUJAN - Yusli Harta, Rika; Mahyaruddin, Mahyaruddin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
Green Super Rice (GSR) is a rice plant that can be cultivated on land that is nutrient efficient, has high yields and is resistant to biotic and abiotic stresses. GSR planting is expected to have adaptability and good yields in conditions of infertile rice fields, often experiencing drought, uncertainty in air supply, low fertility, and disease attacks. The aim of the study was to see the performance of adaptive Green Super Rice in rainfed rice fields. The GSR rice lines will be planted in Bireun, Indonesia. This study used a one-factor Randomized Block Design (RAK) with 3 replications. The treatment factors that were tried were 6 GSR rice lines, the F8 line, from a cross between the Sikuneng variety from Bireun and IRBB27. As a comparison, the national superior variety Inpari 42 was used. There were 21 experiments and each experiment consisted of 2 plant units, one plant as the sample plant. GSR lines which were selected at the Aceh Rice Research Center in the previous planting season. The comparison variety used was Inpari 42. Seedlings aged 21 days after sowing from each line and comparison varieties were planted 1-3 seedlings per hole in a plot measuring 2m x 5m with a spacing of 20 cm x 20 cm. Irrigation relies on rain and water pumps from rainwater reservoirs. variables of plant height (cm), number of productive tillers, heading date or 50% flowering age (HSS), number of filled grain, percentage of filled grain(%), weight of 1,000 grains(g), and yield(t/ Ha).